Big rig - Swenson, Jamie; Young, Ned (New York : Disney*Hyperion Books, 2014)
Frankie, an eighteen-wheel, semi-truck invites the reader to join him on a job, introducing the work, mechanics, and terminology of trucking along the way.
Keywords: Tractor trailers -- Fiction; Trucks -- Fiction